2013
DOI: 10.3906/sag-1209-103
|View full text |Cite
|
Sign up to set email alerts
|

Variations of transverse foramens of cervical vertebrae: a 3-dimensional multidetector CT study

Abstract: Seeds of 14 commonly found plant species from 3 different families (Brassicaceae, Dipsacaceae, and Asteraceae) were investigated for 1000-seed weights (g), total oil (%), total protein (%), total soluble sugar contents (TSS; mg g -1 ), and fatty acid compositions (%). Correlation coefficients of fatty acids from different families were investigated, as well. Palmitic, stearic, oleic, linoleic, linolenic, eicosenoic, and erucic acids were present in varying amounts. Within the family Brassicaceae, only Cardaria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
0
3
1
1
Order By: Relevance
“…As in our study, Degirmenci and Yılmaz determined double TF as the most common variation in cervical vertebrae. Unlike our study, they reported the incidence of hypoplasia as more common (10.4%) and agenesia as less common (4).…”
Section: █ Conclusioncontrasting
confidence: 99%
“…As in our study, Degirmenci and Yılmaz determined double TF as the most common variation in cervical vertebrae. Unlike our study, they reported the incidence of hypoplasia as more common (10.4%) and agenesia as less common (4).…”
Section: █ Conclusioncontrasting
confidence: 99%
“…Regarding the prevalence of DTF, there are studies on different populations ranging from 5.7% to 23.5% in the literature, and most of them are studies using dry bone [23,24]; some of them were made with CT images [25,26]. While some of these studies included all cervical vertebrae, they were made by considering the difference between males and females [25,26]. We also see that some studies were carried out on societies that lived in ancient times [27,28].…”
Section: Discussionmentioning
confidence: 99%
“…Moreira et al (2020) [ 26 ] showed that the parameters from C3 to C7 were similar to those previously reported, with a similar trend about FT dimensions. [ 9 , 14 , 15 , 27 , 28 ] Zibis et al (2016) [ 16 ] studying 700 cervical spine foramen (C1–C7) from angiographic CT images, reported the highest average anteroposterior diameter (APD) in the C6 (6.07 mm on the right and 6.27 mm on the left). In our study, the mean APD ranged from 3.88 to 6.05 mm.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10][11][12][13] Investigators have studied the variability in the dimensions and number of the FT in the cervical vertebrae. [10,[14][15][16] Therefore, it is possible that the trajectory of the vital vascular and neural structures occupying the FT could be distorted owing to the underlying variations. Bible et al (2016) [17] reported that surgical complications can be attributed to a lack of complete knowledge of anatomical variations.…”
Section: Introductionmentioning
confidence: 99%